Temperature and deactivation of microbial faecal indicators during small scale co-composting of faecal matter - Germer, J.; Boh.M.Y.; Schoeffler, M.; Amoah, Philip (Elsevier, 2010)
Small scale co-composting of faecal matter from dry toilet systems with shredded plant material and food waste was investigated in respect to heat development and deactivation of faecal indicators under tropical semiarid conditions. Open (uncovered) co-composting of faecal matter with shredded plant material alone did not generate temperatures high enough (<55 C) to reduce the indicators sufficiently. The addition of food waste and confinement in chambers, built of concrete bricks and wooden boards, improved the composting process significantly. Under these conditions peak temperatures of up to 70 C were achieved and temperatures above 55 C were maintained over 2 weeks. This temperature and time is sufficient to comply with international composting regulations. The reduction of Escherichia coli, Enterococcus faecalis and Salmonella senftenberg in test containment systems placed in the core of the compost piles was very efficient, exceeding 5 log10-units in all cases, but recolonisation from the cooler outer layers appeared to interfere with the sanitisation efficiency of the substrate itself. The addition of a stabilisation period by extending the composting process to over 4 months ensured that the load of E. coli was reduced to less than 103 cfug and salmonella were undetectable.